Surgical tactics for intestinal malrotation in children - Ergashev, Nasriddin Shamsiddinovich; Sattarov, Jamoliddin Bahronovich (European Medical, Health and Pharmaceutical Journal, 2015)
Many aspects of surgical treatment of intestinal malrotation in children remain to be debatable. In the opinion of the majority of the specialists, surgical treatment is required after the diagnosis taking into account serious complications of intestinal malrotation. Purpose. The purpose of this research was to conduct an analysis of surgical tactics and operative treatment method for isolated and associated intestinal malrotations in children. Material and methods. We observed 123 children at the age of one day to 15 years with malrotation during the period of 2002 to 2013. Results. We presented the data from observing 123 children at the age of one day to 15 years with various clinical-anatomic forms of intestinal malrotation over from 2002 to 2013. In 62 patients (50.4%), the evidences of the high intestinal obstruction were prevalent, while 61 (49.6%) showed signs of low intestinal obstruction. 116 patients (94,3%) were given operative intervention: radical – 95(81,9%) and palliative – 21 (18,1%). In 56 % of the cases, various simultaneous surgeries were required. There are proposed differential approaches in relation to anatomic form of malrotation and possibility of the fixation of large intestine in the physiological position. Conclusion. The results obtained from the operative treatment are presented. The lethal outcomes could be reduced from 54.7%, among the patients being observed from 2002 to 2010, to 16,7% in patients being operated during 2011 to 2013.
Keywords: chirurgie trávicího traktu; novorozenec; Infant, Newborn; Observational Studies as Topic; pozorovací studie jako téma; Humans; výběr pacientů; dítě; Child; Patient Selection; Duodenum; Female; Torsion Abnormality; výsledek terapie; lidé; střevní obstrukce; mladiství; torzní deformity; Intestinal Obstruction; předškolní dítě; duodenum; ženské pohlaví; Male; Adolescent; Treatment Outcome; mužské pohlaví; volvulus intestini; Child, Preschool; Digestive System Surgical Procedures; Intestinal Volvulus